Dilemma of Nuclear Power Seekers: Does Failed Attempt to Balance Power Hold Back Future Military Developments in Nuclear Power-seeking States?. Issue 2 (3rd April 2019) - Iwuoha, Victor
ABSTRACT: Can power-seeking states attain strategic significance if they don't depend and hinge their military potentials on foreign powers? While Algeria and Libya pursue clandestine nuclear weapons projects with assistance from foreign nuclear powers, they fail to invigorate their military industrial complex for effective combat readiness. I anchor my analysis on balance of power theory to argue that failed attempts to balance power can hold back military developments in a state. I compare levels of conventional military balance in North Africa to show that even though attempts to acquire nuclear weapons failed terribly in the case of Algeria's and Libya's military development, it did not inherently undercut their conventional military advantage over their neighbors in North Africa.